2020
DOI: 10.1186/s13023-020-01510-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune-mediated thrombotic thrombocytopenic purpura in patients with and without systemic lupus erythematosus: a retrospective study

Abstract: Background: Thrombotic thrombocytopenic purpura (TTP) is associated with more deleterious outcomes in patients with systemic lupus erythematosus (SLE). However, ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) levels and ADAMTS13 inhibitor were not routinely assayed in most previous studies. The objective of this study is to compare the characteristics and outcomes of immune-mediated TTP (iTTP) in patients with and without SLE. Methods: The medical data of 28 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…Among them, 6 cases were secondary to SLE, accounting for 85.71% of secondary TTP. SLE is an autoimmune disease formed by antibodies and immune complexes that mediate organ tissue damage [ 15 ]. SLE is more common in women, accounting for 90% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 6 cases were secondary to SLE, accounting for 85.71% of secondary TTP. SLE is an autoimmune disease formed by antibodies and immune complexes that mediate organ tissue damage [ 15 ]. SLE is more common in women, accounting for 90% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of outcomes of immune-mediated TTP between patients with SLE (n = 8) and those without TTP (n = 10), mortality rates were higher, with a longer duration of treatment before remission, in patients with SLE compared in patients without SLE [16] . However, another study showed the patients with primary TTP (n = 18) had more severe renal involvement compared to patients with SLE-related TTP (n = 10); clinical remission was more frequent and mortality rates were lower in patients with SLE (n = 18) [17] . Although it is difficult to draw firm conclusions due to the small number of study populations, it does not seem to be the case that SLE-related TTP has a worse prognosis than primary TTP.…”
Section: Discussionmentioning
confidence: 96%
“… [16] However, another study showed the patients with primary TTP (n = 18) had more severe renal involvement compared to patients with SLE-related TTP (n = 10); clinical remission was more frequent and mortality rates were lower in patients with SLE (n = 18). [17] Although it is difficult to draw firm conclusions due to the small number of study populations, it does not seem to be the case that SLE-related TTP has a worse prognosis than primary TTP.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth patient was a young female who presented a typical microangiopathic hemolytic anemia [15] with low ADAMTS13 activity whose diagnosis was acquired TTP. Such a rare disease results from autoantibodies against ADAMTS13, a von Willebrandcleaving protease, leading to formation of ultra-large von Willebrand factor multimers with unregulated platelet adhesion and aggregation, disseminated microthrombi, organ ischemia, and high erythrocyte shearing rates [9,15,31,32]. SLE was diagnosed sequentially.…”
mentioning
confidence: 99%
“…SLE was diagnosed sequentially. It is known that acquired TTP can be secondary to other disorders including autoimmune diseases, notably SLE [31]. Actually, SLE can be diagnosed before or concurrently with TTP diagnosis, or even following its recovery [33].…”
mentioning
confidence: 99%